Does integrated reporting enhance the value relevance of organizational capital? Evidence from the South African context - (:unkn) unknown (My University, 2019)
Purpose Despite the growing literature on integrated reporting (IR) adoption and the emphasis on integrated thinking capitals, prior research works only focused on the financial and non-financial reporting rather than the cornerstones of IR. In order to fill this gap, the purpose of this paper is to investigate the value relevance of organizational capital (OC) after the mandatory adoption of IR in South Africa over the period 2006–2015. Design/methodology/approach The authors have used quantitative methods to test the hypotheses. The South African context is unique since the Johannesburg Stock Exchange is the first to mandate listed firms to adopt IR following King III report in March 2010. Findings The findings provide the first evidence, to the best of the authors’ knowledge, on the positive and significant impact of IR adoption on the value relevance of OC. Originality/value The authors contribute to IR literature by providing new insight on the value relevance of one capital from a new perspective addressing the importance of resources as inputs to the business model highlighted by integrated thinking in the IR framework. The findings derive various implications for the International Integrated Reporting Council, managers, decision makers and the research community.
Keywords: African Research